2021
DOI: 10.12659/ajcr.931655
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Managing a Lepromatous Leprosy Patient Complicated with Melioidosis Infection, Dapsone-Induced Methemoglobinemia, Hemolytic Anemia, and Lepra Reaction

Abstract: Patient: Female, 22-year-old Final Diagnosis: Lepromatous leprosy co-infected with melioidosis • complicated by dapsone-induced methaemoglobinaemia and type 2 lepra reaction Symptoms: Cyanosis • fever • jaundice • pallor • skin rash Medication: — Clinical Procedure: — Specialty: Dermatology • Hematology • Infectious Diseases • General and Internal Medicine • Microbiology and Virology Objective: Unusual clinical course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In addition, we noted that 10 virulence genes were significantly over expressed. They are ML0243—Putative acyl-CoA synthetase, ML1014—RNA polymerase sigma factor sigB, ML1076—RNA polymerase sigma factor SigE, ML1128—Diaminopimelate decarboxylase, ML1633—Possible secreted hydrolase, ML1727—O-phosphoserine phosphohydrolase( Acebrón-García-de-Eulate et al, 2021 ), ML1925—Superoxide dismutase [Cu-Zn], ML1954—Pantothenate kinase( Hasan et al, 2004 ), ML2307—Transcriptional regulator and ML2439—Sensory transduction protein RegX3 ( Duthie et al, 2007 ; Sapkota et al, 2010 ; Tang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we noted that 10 virulence genes were significantly over expressed. They are ML0243—Putative acyl-CoA synthetase, ML1014—RNA polymerase sigma factor sigB, ML1076—RNA polymerase sigma factor SigE, ML1128—Diaminopimelate decarboxylase, ML1633—Possible secreted hydrolase, ML1727—O-phosphoserine phosphohydrolase( Acebrón-García-de-Eulate et al, 2021 ), ML1925—Superoxide dismutase [Cu-Zn], ML1954—Pantothenate kinase( Hasan et al, 2004 ), ML2307—Transcriptional regulator and ML2439—Sensory transduction protein RegX3 ( Duthie et al, 2007 ; Sapkota et al, 2010 ; Tang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…AFBs are highly positive. The lesions of LL are numerous with bilateral symmetry over the face, extremities, and trunk [ 58 ]. Lesions may present in any of the stages.…”
Section: Reviewmentioning
confidence: 99%
“…Dapsone (4, 4-diamino-diphenyl sulfone) is a sulfonamide group that is slowly but almost completely absorbed from the gastrointestinal tract, and its central metabolism occurs in the liver (Vinod, Arun, & Dutta, 2013). Methemoglobinemia generally occurs when dapsone is administered at a dose of 200-300 mg/day, and severe methemoglobinemia results from a genetic disorder with deficiency of the enzyme NADH-dependent methemoglobin reductase (Kusumastanto, 2015;Muhaira et al, 2018;Tang et al, 2021). On laboratory examination, it was found that the Hb level was very low when the patient came with shortness of breath in the emergency room.…”
Section: Introductionmentioning
confidence: 99%